Prevalence of Arrhythmias and Risk Factors of Arrhythmias in Patients experiencing them in Azad Jummu Kashmir - Abbasi, Haya Saleem; Abbasi, M Saleem Khan (International Journal of Pathology, 2018)
Objective: Determine the prevalence of arrhythmias in patients presenting to cardiology unit withcardiac complaints at AIMS and assess the risk factors of arrhythmias in those patients.Materials and Methods: The study was conducted at Cardiology department Abbas Institute ofMedical Sciences Muzaffarabad on 100 consecutive patients of both genders presented with variousheart diseases. All patients presenting to cardiology unit of AIMS after confirmation of functionalimpairment of heart in the duration of Feb-April, 2015 were included in the study. The age of thepatients ranged (Mean±SD); 18-100 (56.68±14.08) years. 43% of the subjects were male. A questionnairewas designed regarding Arrhythmias ( ventricular or atrial and their further types), blood pressure,diabetes, physical activities , smoking exposure, Rheumatic heart disease, thyroid disease, Coronaryartery disease (< or equal to 50% stenosis), Myocardial infarction. Body mass index, Xray findings andECG changes were noted. Duration of study was 2 months (1 February to 3 April 2015) .The data wereanalyzed using SPSS 16.Results: Out of 100 enrolled subjects, 30% had arrhythmias, 10% of which had ventricular arrhythmias(7% ventricular tachycardia and 1% with ventricular fibrillation, and 2% with premature ventricularcontraction) and 19% with atrial arrhythmias (15% with atrial fibrillation, 3% with supraventriculartachycardia, 1% with long QT interval), and 1% with complete heart block. Among the patients witharrhythmias 81% had hypertension, 32% had diabetes, 24% had high BMI, 34% had family history ofcoronary artery disease, 46% had MI, about 9% had Rheumatic heart disease, about 11% had smokingexposure, about 3% had thyroid disease, about 40% experienced syncope and 35% had high cholesterol.Conclusion: The prevalence of arrhythmias was 30%. Hypertension and MI were among the mostprevalent risk factors in the arrhythmic patients